FAKTOR -FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Maria Goreti Kewa Lisa,; Zaenal Wafa, (Juremi: Jurnal Riset Ekonomi, 2024)
This study was conducted to determine the factors that influence the timeliness of financial reporting in manufacturing companies listed on the Indonesian Stock Exchange for the period 2021-2023. The sample selection technique used in this study used a purposive sampling technique where the selected sample was based on various considerations and certain criteria that were adjusted to the research objectives. Based on the specified criteria, the researcher obtained 54 data. The results of the study showed that Profitability and Liquidity have a positive effect on the timeliness of financial reporting, while Company Size does not have a significant effect. This finding suggests that companies that are more profitable and liquid tend to be more timely in their financial reporting. Based on these results, investors are expected to pay more attention to the profitability and liquidity of the company before investing, while companies need to maintain the stability of financial statements to increase investor confidence. Further researchers are advised to add other relevant variables, such as Gross Profit Margin or Return on Sales, so that the research results can further enrich the understanding of the timeliness of financial reporting